“Healing hands: Understanding physiotherapists’ knowledge, attitudes and barriers on pressure injury prevention in the medical wards in Jordan” - Enas A. Assaf; Rahaf Alkhresheh; Taher Assaf; Suhair Al-Ghabeesh; Ramasubbamma Ramaiah (PLoS ONE, 2026)
Aim to highlight the physiotherapist's knowledge and attitudes, as well as barriers and related factors affecting Pressure Injury prevention in the medical wards of Jordanian hospitals. Method Cross-sectional correlational study of all physiotherapists working in the three largest governmental hospitals in Jordan (north, capital, south), focusing on medical ward services. A validated instrument for measuring knowledge and attitudes towards pressure injury prevention, as well as selected barriers identified in the literature, was distributed for self-administration. Descriptive analysis, a t-test for two-item variables, and ANOVA (F-value) for variables containing more than two items. Multivariate regression analysis was employed to assess the relationship between the independent variables (demographic factors) and the outcome variables (knowledge, attitude, and perceived barriers). Differences were considered statistically significant at a level of P < 0.05. Results Overall, physiotherapists demonstrate a good understanding and positive attitudes towards the prevention of pressure injuries. However, barriers were marked in the study as the majority considered shortage of resources (94.4%), lack of multidisciplinary team among the health care team (88.9) and uncooperative patients (88.9%) followed by presence of other priorities at work pressure injury prevention (83.3%), and in adequate knowledge (80.6%). Monthly income, working experience, training, and using guidelines were statistically significant predictors of the knowledge score (p values: 0.01, 0.03, 0.02, 0.001, respectively). Age was statistically significant in relation to the attitude score (P < 0.001). None of the demographic characteristics were significantly related to the perceived barriers. Conclusion Physiotherapists can play a significant role in preventing pressure injuries when they possess improved knowledge, as evidenced by their positive attitudes towards preventing pressure injuries for patients in medical wards. However, more attention is recommended to allocate resources and staff, as well as implement policy changes, to enhance a multidisciplinary team approach in working with medical wards, addressing their special needs, overcrowding, and comorbidity among patients. Further research is recommended to assess the roles and barriers faced by physiotherapists in medical wards and other areas.